Alkylnaphthalenes: Priority pollutants or minor contributors to the poor health of marine mussels? - Scarlett, Alan; Clough, R.; West, C.; Lewis, C.; Booth, A.; Rowland, S. (2011)
Alkylnaphthalenes (AN) are relatively water-soluble hydrocarbons which, following spillages of crude oils, have been widely reported in contaminated marine organisms such as mussels. In the present report we show, by tandem-gas chromatography-time-of-flight-mass spectrometry (GC × GC-ToF-MS), that the range of AN in contaminated wild mussels from the UK extends beyond the previously GC resolved isomers to those with at least seven substituent carbon atoms. Since surprisingly little information on AN toxicity to such marine organisms has been reported we synthesized two C 8 AN and measured the toxicity of C 2-8 AN to mussels (clearance rate assay). C 2-3 AN were appreciably toxic (concentration for 50% clearance rate inhibition, 48 h IC 50 1.4-2.6 µmol g -1 dry weight tissue), but several C 4, 6 and C 8 AN, including branched isomers expected to be resistant to biodegradation and more accumulative, were relatively nontoxic (48 h IC 50 > 10 µmol g -1) and longer term exposure (8d) failed to elicit a greater toxic response. The accumulation profiles of AN in laboratory mussels exposed to oil were similar to those of the wild mussels. Moreover, laboratory oil-exposed mussels depurated toxic C 2-3 AN within 5 days in clean water and clearance rates recovered. The latter might imply that, in contrast with branched alkyl benzenes tested previously, AN are of less toxic concern, but such a straightforward conclusion cannot necessarily be drawn; a synthetic branched C 8 AN persisted following depuration and was as toxic to mussels as a C 3 AN (IC 50 1.3 µmol g -1). This indicates that the structures of AN are also important. © 2011 American Chemical Society.